PEMBELAJARAN IPA FISIKA DENGAN PENDEKATAN SAINTIFIK MENGGUNAKAN METODE EKSPERIMEN DITINJAU DARI SIKAP ILMIAH SISWA KELAS VIII5 SMP NEGERI 21 PEKANBARU - Devni Gusliza Sari; Mitri Irianti; M. Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research aimed to determine the level of scientific attitude graders VIII5SMPN 21 pekanbaru with the approach of scientific rendering uses experimental methods on learning subject matter light in the lesson 2013/2014.This type of research is research pre-experimental design in the shape of One-Shot Case Study. Data is collected thatquestionnaire of scientific attitude after the close of students learning to the matter light. A descriptive analysis of the results, obtained an average score of scientific attitude of 37 students of 3,87. It showed that scientific attitude student with the approach of scientific rendering uses experimental methods class VIII5 SMPN 21 pekanbaru having high category.Key words : scientific approach, experimental method, scientific.